Rhetorical Closure. Issue 4 (8th August 2017) - Rood, Craig
Abstract : I call communication that attempts to stop further communication "rhetorical closure." This essay focuses on a form of rhetorical closure that implies character judgments of the interlocutor or audience in order to force assent and delegitimize dissent. Using Ayn Rand's rhetoric as an exemplar, the essay demonstrates what rhetorical closure by character judgment looks like in practice, examines its dynamics, and assesses its enduring appeal.